Ethnobotanical Study of Medicinal Plants used in Skin Diseases in the Area Alamut-Qazvin, Iran - Jinoos Kianifar; Mohammad Azadbakht; Masoud Azadbakht; Ali Davoodi (Institue of Medicinal Plants, ACECR, 2019)
Background: Medicinal plants have been used for treatment of diseases and finding of new drugs. Botanical valuable traditional methods, offer finding new medicinal plants and herbal medicines. Objective: The aim of this study was the identification of important medicinal plants that widely were used by local inhabitants, in the treatment of skin diseases in the area of Alamut-Qazvin, Iran. Method: In this study, the questionnaire was included sections for demographic as well as the medicinal plants information such as local name, how to use, time of harvest and medicinal properties of the plants. The questionnaires were completed by through interviews with 42 traditional botanists and 18 old traditional healers. The data were analyzed by SPSS 20 software. Results: Seventy-five species of medicinal plant were used in the treatment of 9 skin diseases in the area of Alamut-Qazvin, Iran. The most drugs that effecting on 9 known skin diseases are Urtica dioica for corn and eczema, Terminalia chebula in Wart, Cassia fistula in skin leishmaniosis, Crocus sativus in freckles, Nasturtium officinale in Psoriasis, Trachyspermum ammi and Falcaria vulgaris in vitiligo, Matricaria chamomilla in acne and scald skins. In general, most herbal remedies impact on burn patients and the most used plant is Matricaria chamomilla. Ointment 2% was the most used dosage form. Average 2-4 g/day for more than 3 months duration was used for the treatments. Conclusion: The results of this research could be the basis for selection of useful medicinal plants for Phytochemical and pharmacological studies.